Pengaruh Self Talk Positif Terhadap Motivasi Berprestasi Pada Atlet - Safitri, Siti Nabila; Rahmah, Jihan Hafizhah; Yulitri, Sherly; Addini, Khalisha Nafila; Aulia, Prima (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2024)
Achievement motivation has a very important role in determining the success of an athlete. Achievement motivation not only encourages athletes to continue practicing and competing vigorously, but also helps them overcome the challenges and obstacles faced during the process. One method that can be done to increase achievement motivation is to do positive self-talk. This study aims to determine the effect of positive self-talk on achievement motivation in athletes. This study used a quasi-experimental method with a non-equivalent control group design (unequal pre-test-post-test). The research subjects were 24 students of class XI.F athletes from various sports at SMA N 4 SUMBAR which were then divided into two groups, namely the experimental group (12 students) and the control group (12 students). Data were collected through pretest and posttest questionnaires measuring two variables of self-talk and achievement motivation, using the Likert Model scale in both groups. The data analysis technique used was using the Paired Sample T-Test test method with the help of SPSS for windows 1.18.1.. The results of the Paired Sample T-Test test analysis showed a Sig. (2-tailed) of 0.000 is smaller than the probability of 0.05 (0.000 <0.05), so it can be said that the hypothesis is accepted. Based on these results, it can be concluded that positive self-talk has a significant influence on achievement motivation in athletes.